Episodic Future Thinking Is Related to Impulsive Decision Making in Healthy Adolescents. Issue 5 (25th June 2015) - Bromberg, Uli; Wiehler, Antonius; Peters, Jan
<x xml:space="preserve">Abstract</x> Delay discounting is a stable trait measure of impulsivity. Engaging in episodic future thinking (EFT) can reduce discounting, but whether individual differences in discounting are associated with differences in future thinking remains unclear. Here, this association was tested in healthy adolescents (n = 49, age range = 12–16 years, fluent German speakers, from a large German city). Data collection was between December 2011 and December 2012. Vividness of EFT (assessed via the Autobiographical Memory Interview) was negatively correlated with discounting (r = −.41, 95% CI [−.63, −.13], r2 = .17). Regression analyses confirmed that this association was stable when controlling for additional variables, including hormonal measures of pubertal maturation and intelligence. EFT may attenuate impulsivity in young people at risk of engaging in problematic behavior.